PENGEMBANGAN KETERAMPILAN GERAK TARI LITERASI TERHADAP KEMAMPUAN MEMBACA HURUF SISWA KELAS 1 SEKOLAH DASAR NEGERI BANJARWANGI - Tesa Muliawati; Anggia Suci Pratiwi; Rahmat Permana (PIWURUK: Jurnal Sekolah Dasar, 2021)
This study aims to determine the development of literacy dance skills on the ability to read letters grade 1 students of Banjarwangi State Elementary School. Learning to read in class 1 Banjarwangi State Elementary School there are obstacles namely when the teacher teaches reading and lack of confidence and student activity, lack of reading skills and lack of enthusiasm so that teachers experience obstacles and limitations in making learning media that is truly suitable and in accordance with the material to be taught. This study aims to develop and test the effectiveness of literacy dance skills on the ability to read letters of grade 1 students of Banjarwangi State Elementary School. The formulation of the problem in this research is how to develop literacy dance skills on the ability to read letters and instill character in first grade students of Banjarwangi State Elementary School? The research method used is the development method with research or development design or R&D (Research and Development). This research was conducted at the Banjarwangi Public Elementary School in the District of Salopa in Tasikmalaya Regency in grade 1 students, the sample taken in this study was 9 students. Small groups of 1 person and large groups of 8 people. Data collection techniques in this study used a Questionnaire and Test dance literacy. The results of the study that literacy dance moves are suitable for the reading ability of grade 1 students of Banjarwangi State Elementary School.